Saberes construídos pelos professores nas práticas docentes da educação de jovens e adultos - Cunha Júnior, Adenilson Souza (2012)
This research deals with the knowledge built by the teachers in their teaching practices when working in Young and Adults Education (EJA). These practices constitute a repertoire of knowledge, that through their experiences, the teachers rethink and adapt based on the peculiarities of his students of young and adult education and on the reflection they make about their own teaching practices. The study on the knowledge that teachers build on their teaching practices indicates the possibility of taking the experiences of teachers as a starting point for discussions, debates and reflections on the training of teachers working in teaching modality of Youth and Adults Education. The investigation focused on the following question: how teachers build the knowledge when acting in the mode of teaching Youth and Adults? It had as main objective to understand the process of building of knowledge in teaching practice of Youth and Adults. The phenomenological approach had a qualitative nature, and was the theoretical-methodological way adopted. The research was conducted with five teachers who work in classes of Youth and Adults Education in municipal schools in the municipality of Vitoria da Conquista (BA). As an instrument for data collection, we used semi-structured interview. From the data obtained, the experiential knowledge emerged, which were used as an analytical category. The experiential knowledge concerns the use of language and methodologies appropriate to the students, the contextualization of content, and social recovery of the students of young and adult education. The results of the research have revealed that when working in EJA the teacher builds practical skills, developed in their pedagogical actions from their experience, skills acquired in the daily activities in this teaching modality. The experiences identified and analyzed demand, from our point of view, the development of a rigorous training process (initial and continuing), scientific-technical and politically planned, requiring from the training instances the investment needed to rework the educational policies and thus reframe the educational experience for this type of education.